Promoting biodiversity - Savulescu, J; Gyngell, C (Springer, 2016)
Advances in biotechnology mean that it may soon be possible to recreate previously extinct species. This has led to an emerging debate within bioethics about whether we ought to reintroduce extinct species into our ecosystems. In this paper we discuss the role that biodiversity could play in this debate. Many believe that biodiversity is a good that should be protected. We argue that if biodiversity is a good, then this suggests it should also be promoted, including by reintroducing previously extinct species. We begin by outlining different ways in which biodiversity could be conceptualised, and then analyse various accounts of its value. We suggest no approach justifies an asymmetry between “protecting” biodiversity by conserving species alive today, and “creating” biodiversity by introducing previously extinct species. This suggests that if we have reasons stemming from biodiversity to protect species from extinction, we will have similar reasons to reintroduce previously extinct species. We close by asking whether arguments from biodiversity speak in favour of introducing some novel species into the ecosystem.